Optically detected magnetic resonance investigations of diluted magnetic semiconductors - Godlewski, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Mechanisms responsible for optical detection of Mn2+ magnetic resonance in II-Mn-VI compounds are discussed. We describe several of these mechanisms. The most efficient one which is due to very efficient spin-flip interactions of localized magnetic moments of Mn2+ ions with free carriers is important at increased excitation density.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 271-283
Keywords: optyka; magnetic resonance; diluted magnetic semiconductors; spin flip interactions; spin dynamics